1985
DOI: 10.1071/ar9850361
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wheat density and spatial arrangement on annual ryegrass, Lolium rigidum Gaudin, competition

Abstract: The influence of wheat (Triticum aestivum L.) planting arrangement and density on the competitive effect of the weed, annual ryegrass (Lolium rigidum Gaudin), was examined in field experiments over three climatically contrasting years on the central western slopes of New South Wales. Results for three experiments conformed to a common trend. Geometrical arrangement of the crop (rectangularities of 1 to 6.4) at any one of a range of crop densities had no significant effect (P > 0.05) on ryegrass competition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 0 publications
3
52
1
1
Order By: Relevance
“…To a lesser extent, the number of grains per ear (GUI00 and WH96) also contributed to the yield losses recorded. The ability of weeds to affect crop grain number and tiller number is well established [5,20]. Thousand grain weight was the yield component least affected by weed competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent, the number of grains per ear (GUI00 and WH96) also contributed to the yield losses recorded. The ability of weeds to affect crop grain number and tiller number is well established [5,20]. Thousand grain weight was the yield component least affected by weed competition.…”
Section: Discussionmentioning
confidence: 99%
“…Lemerle et al [18] have shown that the genetic variability present in Australian wheat varieties can be used to increase competitiveness of the crop. Alternatively, manipulating crop agronomy, such as increasing the crop seeding rate [20,29], may be a practical alternative.…”
Section: Introductionmentioning
confidence: 99%
“…On black earth soils on the Darling Downs in Queensland, large reductions in wild oat biomass and seed production and a consequent increase in wheat grain yield due to increase in wheat density have been reported. 29 In a later study, Medd et al 30 in New South Wales found that competitive e †ects of annual ryegrass on wheat were substantially reduced by increasing wheat sowing density.…”
Section: Increased Crop Density For Weed Suppressionmentioning
confidence: 98%
“…However, the higher value observed in 2010/11 in F1 could be attributed to other factors. As has been established for other grass weeds (Medd et al, 1985;Cousens et al, 1988;Izquierdo et al, 2003), the strongest crop competition takes place early in the growing seasons, affecting weed tillering. The stress caused by lack of rain until February in the winter of 2010/11 reduced the competitive effect of the crop and, though the plants were smaller, they had more tillers.…”
Section: Vegetative and Reproductive Fitnessmentioning
confidence: 99%